(untitled) (Research, Society and Development, 2022)
Introduction: Leprosy is a chronic infectious disease caused by M. leprae, it has a predilection for affecting the skin and peripheral nerves, which becomes a characteristic sign of the disease, making it easy to identify in most cases. However, it presents neurological damage that depends on the degree and severity of the disease. Considered a public health problem, especially in emerging countries, such as Brazil and similar countries. Methods: This is a descriptive study on the profile of leprosy cases among the states of the Northeast region from 2015 to 2017. Secondary data obtained from the Notifiable Diseases Information System (SINAN) of the Department of Informatics of the Unified Health System were used. Health (DATASUS), at the website (http://www.datasus.gov.br), collected in May 2020. Results: Between 2005 and 2017, there were 186,559 new cases of leprosy in northeastern Brazil, with 52.6% ( n=98,174) in males and 47.4% (n=88,374) in females. Regarding the age group, 8.5% (n=15,879) of the cases occurred in children under 15 years old, 54.5% (n=101,534) occurred between 15 and 49 years old and 37.1% (n=69,142) in older adults. of 49 years. Conclusion: The analysis of leprosy cases notified from 2015 to 2017 showed a greater number of cases in 2016, where in this period the notifications by the male gender predominated, especially in the range from 15 to 49 years old and related injuries and disabilities are the most common. common ways in these cases.